Dual-Band MIMO Antenna Design for 5G Smartphones Mobile Communications - Atta Ullah; Naser Ojaroudi Parchin; Mohamed Abdul-Al; Waqas Manan; Abubakar Salisu; Ibrahim Gharbia; Chan Hwang See; Raed Abd-Alhameed (Journal of Techniques)
In this research, an innovative L-shape slot that is fed by F-shape dual-band six-Elements multiple-input multiple-output (MIMO) antenna for mobile phones that operate in a 5G spectrum is demonstrated. This proposed antenna has six antenna elements that can operate in dual band sub-6 GHz for 5G band spectrums at 3.42–3.77 GHz and at 5.30–5.63 GHz. Every antenna element has an L-shaped slot in the ground fed by the same feedline that support the matching of the F-shaped microstrip lines. Important features of the anticipated layout are examined. It provides excellent efficiency at the operation band, appropriate isolation, adequate radiation coverage, and good S-parameters. Ant 3's provided the maximum return loss at 3.6 GHz which is -35 dB, whereas Ant 5 and Ant 6 provide the highest return losses at 5.4 GHz which is -38dB of the suggested dual-band frequency of 5G smartphones. To validate the exactness of the constructed MIMO antenna performances, the sample prototyping and experimentally measured outcomes were carried out in the Lab. Both simulated and measure result assessments revealed an extremely excellent understanding of both results. satisfactory input impedance and mutual coupling characteristics. Future smartphones can leverage the proposed design for high data-rate cellular connectivity because of these appealing properties.